(untitled) (Singaporean Journal of Business Economics and Management, 2014)
Cities in Nigeria, as elsewhere, have historically exerted potent influences on the countryside. The northern city-states for instance played a major role in the distribution of human population and economic activity throughout the savanna region. As citadels and centers of power and conquest, they caused depopulation in some regions, notably those subject to conquest and raiding, and population concentration in other areas. The low populations of the middle belt savanna probably resulted from the raiding and the conquests of the Hausa and Fulani city-states. The subsequent regrowth of bush land is thought to have led to a resurgence of tsetse flies and other disease vectors, which inhibited attempts to repopulate the region. The complementary effect was to increase population in zones of relative security, either areas under the protection of the dominant political states or areas of refuge, such as hill masses, which were difficult for armed horsemen to conquer. Among the most important interactions between rural and urban areas through the 1980s till date in Nigeria and most other parts of Africa were the demographic impacts of urban migration on rural areas. This is because the great majority of migrants were men of working age, the rural areas from which they came were left with a demographically unbalanced population of women, younger children, and older people. This phenomenon was not new to Nigeria and had been evident in parts of the country since long before independence. The paper discusses the major conceptual issues in a thematic form by identifying the factors that led to the growth of cities, and concludes by positing that we are not saying that cities were absent in pre-industrial, pre-capitalist or pre-nation state societies. Rather, it was the combination of those influences that gave rise to accelerated urbanization, a new role for the city within the larger society and, hence, they city as we know it today.